The effects of PISA on global basic education reform: a systematic literature review - Li, Jian; Xue, Eryong; Guo, Siyuan (Humanities and Social Sciences Communications, 2025)
The Program for International Student Assessment (PISA) is a vehicle for promoting students’ learning that plays a significant role in basic education reform globally. Few studies have used the transnational academic achievements of PISA as evidence to systematically summarize the primary motivation behind PISA’s participation in global decision-making and the core issues of PISA’s impact on education reform. Using a systematic review approach, we aimed to analyze findings from empirical research about the impact of PISA on global basic education policies and to provide an overview of the effects of PISA on global basic education reform. The Social Sciences Citation Index (SSCI) and Scopus databases were searched for empirical research written in English, focusing on basic education, and including search terms such as PISA, educational reform, and policy. A total of 85 studies were included in the review and systematically synthesized to determine the effect of PISA on global basic education reform. PISA drives policy discussions on education quality and equity through its pursuit of educational quality, data-based comparative analysis, and evidence-based research paradigms. PISA’s impact has extended far beyond its original function of measuring the quality of education among countries, and it profoundly affects global education governance through ‘soft’ governance of the education system. We present a specific mechanism model of PISA’s impact on the development of education policies that demonstrates the two-way interaction between PISA and education reform, providing a theoretical reference for future academic research on education reform linked to PISA.